2021
DOI: 10.1002/chem.202101408
|View full text |Cite
|
Sign up to set email alerts
|

Iminosugar C‐Glycosides Work as Pharmacological Chaperones of NAGLU, a Glycosidase Involved in MPS IIIB Rare Disease**

Abstract: Mucopolysaccharidosis type IIIB is a devastating neurological disease caused by a lack of the lysosomal enzyme, α‐N‐acetylglucosaminidase (NAGLU), leading to a toxic accumulation of heparan sulfate. Herein we explored a pharmacological chaperone approach to enhance the residual activity of NAGLU in patient fibroblasts. Capitalizing on the three‐dimensional structures of two modest homoiminosugar‐based NAGLU inhibitors in complex with bacterial homolog of NAGLU, CpGH89, we have synthesized a library of 17 imino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“… 26 , 27 In this field, the activity of some iminosugar derivatives acting as pharmacological chaperones for the treatment of MPS II, III, and IV was evaluated. 28 31 Furthermore, an interesting application of iminosugars in MPSs involves the assumption that inhibition of ganglioside secondary storage can represent a therapeutic strategy for patients with neurological involvement. On these bases, miglustat was evaluated as a substrate-reducing agent for Sanfilippo diseases due to its ability to interfere with glycosphingolipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 27 In this field, the activity of some iminosugar derivatives acting as pharmacological chaperones for the treatment of MPS II, III, and IV was evaluated. 28 31 Furthermore, an interesting application of iminosugars in MPSs involves the assumption that inhibition of ganglioside secondary storage can represent a therapeutic strategy for patients with neurological involvement. On these bases, miglustat was evaluated as a substrate-reducing agent for Sanfilippo diseases due to its ability to interfere with glycosphingolipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, iminosugars, glycomimetics with an amino function replacing the endocyclic oxygen of natural carbohydrates, exhibited a notable pharmacological potential in the LSD treatment stewardship, thanks to their ability to interact with carbohydrate-processing enzymes and alter their properties. In particular, some iminosugars have found application in the treatment of LSDs either for their ability to inhibit substrate synthesis (SRT) , and consequent lysosomal accumulation or to bind, reversibly and at sub-inhibitory concentrations, mutated lysosomal enzymes, thus enhancing or restoring their function (pharmacological chaperone therapyPCT). , To date, two iminosugars are commercially available for the treatment of LSDs: ZAVESCA (miglustat, also known as d -NBDNJ, N -butyl- d -deoxynojirimycin, compound 2 ) (Figure ), licensed within the SRT for the treatment of type I Gaucher’s disease , and Niemann–Pick type C disease, and Galafold (migalastat, also known as DGJ, 1-deoxygalactonojirimycin), at present the only approved pharmacological chaperone for Fabry disease. , In addition, many other iminosugars have been evaluated for their use as drug candidates in different LSDs, including MPSs. , In this field, the activity of some iminosugar derivatives acting as pharmacological chaperones for the treatment of MPS II, III, and IV was evaluated. Furthermore, an interesting application of iminosugars in MPSs involves the assumption that inhibition of ganglioside secondary storage can represent a therapeutic strategy for patients with neurological involvement. On these bases, miglustat was evaluated as a substrate-reducing agent for Sanfilippo diseases due to its ability to interfere with glycosphingolipid metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, studies investigating pharmacological chaperones for MPS IIIB have reported interesting findings. [19][20] In a previous study by Zhu, et al, [19] the results of crystallization of CpGH89, a bacterial homolog of NAGLU, with the inminosugars α-HNJNAc and β-HNJNAc was used to synthesize a series of derivatives by introducing alkyl/aryl groups at the pseudoanomeric position of the inminosugars. Testing these derivatives on MPS IIIB fibroblasts (GM01426) revealed that some of the synthesized compounds exhibited a modest increase in enzyme activity (1.1-to 1.6-fold) compared to untreated fibroblasts at a concentration of 100 μM.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, β-homoiminosugar proved to act as the most potent PC, eliciting, at its optimal concentration, a 2.4-fold increase of the activity in mutant NAGLU. [19] A recent report showed a set of N-substituted Liminosugars able to reduce the HS levels in several cellular models (including MPS IIIB fibroblasts) and increased both NAGLU protein and activity. [20] Noteworthy, the authors suggested that these molecules may act both reducing the HS synthesis and as a nonactive site PCs.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic instability of aminoacetal functionalities makes impractical the synthesis of iminosugar O -glycosides or of analogues having other heteroatom substituents at the pseudoanomeric position. Instead, aglycon-like appendages have been incorporated through N -substitution and C -branching approaches, which accounts for the two major subclasses of iminosugar derivatives on record.…”
Section: Introductionmentioning
confidence: 99%